2015
DOI: 10.1515/admin-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Local government reform – Plus ça change, plus c’est la même chose?

Abstract: The perceived deficiencies in Ireland’s local government system have frequently been diagnosed, resulting in reports, White and Green Papers and action plans. This article reviews the main reform trajectories, paying particular attention to developments since 1971 and demonstrating that the reforms which did occur were affected by national and international developments. The form, functioning and financing of local government were recurrent themes in the reform documents, and these aspects are specifically exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The follow-up reports by the Local Government Efficiency Review Implementation Group (2012Group ( , 2013 showed that the local government sector achieved notable reductions in expenditure and staffing levels. There is some dispute over the precise figure for the decline in staffing, with Quinn (2015) claiming it was 24 per cent and Callanan (2016) stating it was 21 per cent. Whichever figure we take, it is worth noting that local government suffered 'the largest reduction in staff numbers across the public sector, and compared to a 4 per cent fall in those working in education and a 7 per cent fall in those working in central government ministries and departments' (Boyle, 2014).…”
Section: Irish Local Government After the Financial Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…The follow-up reports by the Local Government Efficiency Review Implementation Group (2012Group ( , 2013 showed that the local government sector achieved notable reductions in expenditure and staffing levels. There is some dispute over the precise figure for the decline in staffing, with Quinn (2015) claiming it was 24 per cent and Callanan (2016) stating it was 21 per cent. Whichever figure we take, it is worth noting that local government suffered 'the largest reduction in staff numbers across the public sector, and compared to a 4 per cent fall in those working in education and a 7 per cent fall in those working in central government ministries and departments' (Boyle, 2014).…”
Section: Irish Local Government After the Financial Crisismentioning
confidence: 99%
“…Secondly, while there is a tendency to focus on the lack of functions under the remit of local authorities, there have been significant changes in how councils fulfil existing functions. After the recommendations of the Local Government Efficiency Review Group in 2010, we have seen changes to procurement systems, a reduction in the use of consultants and an increasing number of shared-service projects in areas such as HR, payroll, pensions and ICT (see Callanan, 2016;Quinn, 2015). For example, Laois County Council now operates the payroll and superannuation functions for virtually all of the local authorities.…”
Section: Functionsmentioning
confidence: 99%
“…Recurring themes in successive proposals and policy initiatives around local government reform over the decades have included issues such as territorial restructuring at regional level, city/county level and sub-county level, greater financial resources and autonomy, governance and management reforms, changes to the functional responsibilities of local government, and an enhanced developmental role for local government, including the bringing together of a range of governmental and non-governmental actors at local level (for a useful overview, see Quinn, 2015). This article looks at past and current reform themes, but also takes a slightly more speculative perspective to try to reflect on some of the longer-term trends that may have an influence on local government reform into the future.…”
Section: Introductionmentioning
confidence: 99%